Modelling Driver-Pedestrian Interaction At Raised Crosswalks - Jason King Teck Qing,; Basil David Daniel,; Paikun,; Sri Wiwoho Mudjanarko,; Aleeya Erdyna Mohd Noor Azmi, (International Journal of Integrated Engineering, 2025)
The concept of traffic calming emerged in the 1960s as a response to road safety concerns and the need to improve pedestrian environments. Raised crosswalks became a popular measure in the late 20th century, providing a physical restraint to counter potentially dangerous conflicts between fast moving vehicles and pedestrians at crosswalks, and  to enhance environments that promote walking as a mode of transport. Understanding the dynamics of driver-pedestrian interaction at raised crosswalks is crucial for promoting road safety and efficient urban mobility. This research was conducted in Universiti Tun Hussein Onn Malaysia (UTHM) campus to investigate driver yielding behavior and pedestrian attitudes towards drivers to forecast driver yielding probabilities at raised crosswalks using logit modelling. Data collection was conducted at a raised crosswalk in front of the Faculty of Civil Engineering and Built Environment. Five contributory variables that were historically found to have affected driver yielding behaviour at pedestrian crossing facilities, i.e., gap size, vehicle speed, position of pedestrians, position of vehicles and number of pedestrians waiting, were chosen to develop the logit model. Two equations were developed as part of the analytical process. The first being a yielding function that was developed to describe the driver yielding behavior with the selected variables, and the second, a logit function that was developed to predict the probability of drivers yielding to pedestrians at the crosswalk. Results showed that all five variables had significantly influenced drivers’ yielding decision, with p values less than 0.05. The model shows strong validity, with an average accuracy rate of 90.83%. It was found that yielding behavior among drivers increases with larger gap sizes, higher vehicle speed and vehicles located on the near lane or on both lanes. Based on these findings, it can be concluded that conflicts between vehicles and pedestrians at raised crosswalks can be reduced, hence promoting harmonious and safe road user interactions.